Administração pública 4.0 : o dever de proteção de dados pessoais interligado aos deveres de acesso à informação, publicidade e cibertransparência - Santos, Nathalia Mylena Farias (2023)
Nowadays, society is experiencing the so-called Fourth Industrial Revolution or Revolution 4.0 where new disruptive technologies gain relevant prominence. In this context, the role of Public Administration stands out with the digital provision of public services and the need to ensure the fundamental rights and guarantees of citizens, as well as administrative constitutional duties. In view of the above, the present work aims to demonstrate the impacts of state action in cyberspace, that is, Public Administration 4.0, correlating the fundamental right to the protection of personal data and the duties of public access to information, publicity and cybertransparency. Thus, the contribution of this research reveals the need to adopt mechanisms of Governance, Data Governance, good practices and compliance with a view to ensuring due respect for the aforementioned constitutional duties. Furthermore, instruments that enable these mechanisms are also highlighted, such as the 5W+1H+SHOW ME techniques, lean approach, benchmarking and PDCA cycle. Therefore, the type of research employed was exploratory research, with the objective of investigating content related to the proposed theme. As for the approach, the qualitative methodology was used, since the analysis of qualitative aspects on the subject was sought, such as normative instruments and doctrinal and jurisprudential understandings. With regard to the technique used as an instrument to conduct the research objectives, bibliographical research is cited, due to the use of already published materials such as books, articles and periodicals, as well as the use of legislation related to the theme.